Impaired Sensorimotor Gating Using the Acoustic Prepulse Inhibition Paradigm in Individuals at a Clinical High Risk for Psychosis. (3rd August 2020) - Bo, Qijing; Mao, Zhen; Tian, Qing; Yang, Ningbo; Li, Xianbin; Dong, Fang; Zhou, Fuchun; Li, Liang; Wang, Chuanyue
Abstract: Many robust studies have investigated prepulse inhibition (PPI) in patients with schizophrenia. Recent evidence indicates that PPI may help identify individuals who are at clinical high risk for psychosis (CHR). Selective attention to prepulse stimulus can specifically enhance PPI in healthy subjects; however, this enhancement effect is not observed in patients with schizophrenia. Modified PPI measurement with selective attentional modulation using perceived spatial separation (PSS) condition may be a more robust and sensitive index of PPI impairment in CHR individuals. The current study investigated an improved PSSPPI condition in CHR individuals compared with patients with first-episode schizophrenia (FES) and healthy controls (HC) and evaluated the accuracy of PPI in predicting CHR from HC. We included 53 FESs, 55 CHR individuals, and 53 HCs. CHRs were rated on the Structured Interview for Prodromal Syndromes. The measures of perceived spatial co-location PPI (PSCPPI) and PSSPPI conditions were applied using 60- and 120-ms lead intervals. Compared with HC, the CHR group had lower PSSPPI level (Inter-stimulus interval [ISI] = 60 ms, P < .001; ISI = 120 ms, P < .001). PSSPPI showed an effect size (ES) between CHR and HC (ISI = 60 ms, Cohen's d = 0.91; ISI = 120 ms, Cohen's d = 0.98); on PSSPPI using 60-ms lead interval, ES grade increased from CHR to FES. The area under the receiver operating characteristic curve for PSSPPI was greater than that for PSCPPI. CHR individuals showed a PSSPPI deficit similar to FES, with greater ES and sensitivity. PSSPPI appears a promising objective approach for preliminary identification of CHR individuals.